A Novel Adaptive Search Range Algorithm for Motion Estimation Based on H.264 - Yuan, Youwei; Li, Wuyi; Wang, Shiyu (Journal of Science and Technology, 2011)
Motion estimation (ME) is very vital to video compression. Due to the adoption of the high precision of motion vector (MV) in H.264 encoder, the computational cost increases rapidly, and ME takes about 60% of the whole encoding time. In order to accommodate the new variable block size motion estimation strategy adopted in H.264, this paper proposes a novel adaptive search range(ASR) algorithm as a optimized part based on UMHexagonS. Not only we utilize the median_MVP and interframe information in our ASR algorithm but also a penalty function is included. Experimental results indicate that our proposed method reduces the computational complexity in a certain degree and enhances encoding efficiency but has few changes in the reconstructed image quality and bit rate.